Pembuatan Bioetanol Dari Kulit Nanas (ananas comosus l.) Menggunakan Enzim Selulase Dan Yeast Saccharomyces Cerevisiae Dengan Proses Simultaneous Sacharificatian and Fermentation (SSF) - Sally Mandari; Elvi Yenie; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
One of energy source alternative that can be used as a substitute for fossil fuel-based energy, is bioethanol. Bioethanol is biochemistry fluid from fermentation process of sugars from carbohydrate sources by using microorganisms. The raw material of bioethanol production is very diverse, like pineapple peel. Pineapple peel can be used as raw material for bioethanol production because contain of fiber, carbohydrates and sugar. This study aims to make bioethanol from pineapple peel with Sacharificatian Simultaneous and Fermentation (SSF) process with cellulase enzyme variation are 1%, 3%, 5%, 7%, and 10% v / v substrate and fermentation time are 2, 3, and 4 days. From the research is obtained the highest bioethanol concentration is 8% on the addition of cellulase enzymes 10% v / v substrate with 3 days fermentation time. Keyword: Bioethanol; Pineapple Peel; Saccharomyces Cerevisiae; Cellulase; SSF